Effects of Nitrogen Application Rate on Nitrogen Uptake and Utilization in Waxy Sorghum Under Waxy Sorghum–Soybean Intercropping Systems - Can Wang; Siyu Chen; Fangli Peng; Qiang Zhao; Jie Gao; Lingbo Zhou; Guobing Zhang; Mingbo Shao (Plants)
Waxy sorghum–soybean intercropping is a sustainable and intensive farming system in southwest China. However, there is limited knowledge about the effects of intercropped soybean combined with nitrogen application on nitrogen uptake and utilization in waxy sorghum. A two-year (2023 and 2024) field experiment was carried out using a randomized complete block design with three planting patterns and three nitrogen application rates to explore the responses of grain yield formation and nitrogen uptake, accumulation, transportation, metabolism physiology, and utilization of waxy sorghum for intercropped soybean combined with nitrogen application. Planting patterns included sole cropped waxy sorghum (SCW), sole cropped soybean (SCS), and waxy sorghum intercropped with soybean (WSI), and nitrogen application rates included zero nitrogen (N0), medium nitrogen (N1), and high nitrogen (N2). Results showed that the dry matter accumulation amount, nitrogen content, nitrogen accumulation amount, nitrogen transportation amount, nitrogen transportation rate, contribution rate of nitrogen transportation to grains, nitrogen metabolizing enzymes activities (including nitrate reductase, nitrite reductase, glutamine synthetase, glutamate synthetase, glutamate dehydrogenase, and glutamic-pyruvic transaminase), and active substances contents (including soluble sugar, soluble protein, and free amino acid) in various organs of waxy sorghum among planting patterns and nitrogen application rates were in the order of WSI > SCW and N1 > N2 > N0, respectively. In addition, the nitrogen uptake efficiency, nitrogen agronomy efficiency, nitrogen apparent efficiency, nitrogen recovery efficiency, nitrogen partial factor productivity, and nitrogen contribution rate of waxy sorghum among planting patterns and nitrogen application rates were in the sequence of WSI > SCW and N1 > N2, respectively. The changes in above traits resulted in the WSI-N1 treatment obtaining the highest grain yield (6020.66 kg ha−1 in 2023 and 6159.81 kg ha−1 in 2024), grain weight per spike (65.22 g in 2023 and 64.51 g in 2024), 1000-grain weight (23.14 g in 2023 and 23.18 g in 2024) of waxy sorghum, and land equivalent ratio (1.41 in 2023 and 1.44 in 2024). Overall, waxy sorghum intercropped with soybean combined with medium nitrogen application (220 kg ha−1 for waxy sorghum and 18 kg ha−1 for soybean) can help enhance the nitrogen uptake and utilization of waxy sorghum by improving nitrogen metabolizing enzymes’ activities and active substances’ contents, thereby promoting its productivity.